2021
DOI: 10.1007/s11356-021-16990-w
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions and mitigation potential of hybrid maize seed production in northwestern China

Abstract: Although hybrid maize seed production is one of the most important agriculture systems worldwide, its greenhouse gas (GHG) emissions and potential mitigation measures have not been studied. In this study, we used life cycle assessment (LCA) to quantify the GHG emissions of 150 farmers run by 6 companies in an area of northwest China known for hybrid maize seed production. The results indicated that the average reactive nitrogen (Nr) losses and GHG emissions from hybrid maize seed production were 53 kg N ha − 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Biochar application alone had a slight effect on rice yield without N fertilizer application in our study (Figure 4a), which was consistent with the results of Ye et al (2020). B2N significantly increased rice yield by 23% (Figure 4a), which was consistent with the results of Liu, Li, et al (2022) and Liu, Zhang, et al (2022). In general, biochar combined with N fertilizer produces the maximum yield (Figure 4a), which may be attributed to the promotion of microbial activity, increased nutrient release, and prevention of nitrogen leaching (Li et al, 2015).…”
Section: And Ghgisupporting
confidence: 90%
See 3 more Smart Citations
“…Biochar application alone had a slight effect on rice yield without N fertilizer application in our study (Figure 4a), which was consistent with the results of Ye et al (2020). B2N significantly increased rice yield by 23% (Figure 4a), which was consistent with the results of Liu, Li, et al (2022) and Liu, Zhang, et al (2022). In general, biochar combined with N fertilizer produces the maximum yield (Figure 4a), which may be attributed to the promotion of microbial activity, increased nutrient release, and prevention of nitrogen leaching (Li et al, 2015).…”
Section: And Ghgisupporting
confidence: 90%
“…(2022) and Liu, Zhang, et al. (2022). In general, biochar combined with N fertilizer produces the maximum yield (Figure 4a), which may be attributed to the promotion of microbial activity, increased nutrient release, and prevention of nitrogen leaching (Li et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are also consistent with those of Rehman et al ( 2020 ), Rehman et al ( 2021a ), Warsame et al ( 2021 ), and Zhang et al ( 2021 ), all of whom found that carbon dioxide emissions have a considerable positive impact on maize output. Carbon dioxide emissions, on the other hand, have a detrimental influence on maize output (Chen et al 2020 ; Feng et al 2020 ; Liu et al 2022 ). Because irrigation is a potential remedy for ensuring a consistent water supply and mitigating heat stress, it is critical to expand the use of groundwater irrigation in measuring the carbon dioxide emissions of agricultural production and underpinning the prospects for their reduction to sustainably develop farming strategies that increase yield with a minimal environmental cost.…”
Section: Resultsmentioning
confidence: 99%